iCARE (IRC Consultancy and Reference Service) - Suito, Helmi Iskandar; Mahmud, Zaidah (Universiti Teknologi MARA, Kedah, 2017)
Reference service is one of the key components in library environment that acts as the frontline in providing assistance to library users either in using library services or finding information. Over the years reference service has evolved in line with changes in information and communication technology in order to reach all of library users. [n academic environment, particularly in higher learning institution, the shift from traditional teaching and learning to technology-based delivery has resulted in changes in library users' behaviour and demand. Along with the fast growing information and communication technology reference services need to adapt to the changes and cater to the new demands. An integrated system is needed to provide more effective and efficient service to cater for new generation of customers through use of multi-channel communication system. UTP Information Resource Centre (lRC) has adopted a new system to meet this challenge. iCARE is an online reference platform that integrates various communication channels including social media, helpdesk platform and FAQ portal. Users can communicate with IRC through FAQ portal, online enquiry form, online chats, Facebook, Twitter and email. This platform enables IRC to enhance current business proses that leads to effective and efficient services to customers, offer 24/7 reference services and also increase the ROI for IRC.